Experimental and Theoretical Investigation of the Synthesis, Electronic and Magnetic Properties of MnFe2O4 Spinel Ferrite - Khaoula Aghrich; Sara Mtougui; Fayçal Goumrhar; Mustapha Abdellaoui; Nabila Mamouni; Mohammed Fekhaoui; Amine El Moutaouakil; Omar Mounkachi (Energies, 2022)
MnFe2O4 ferrite nanoparticle was synthesized via the sol–gel method, and structural, morphology and magnetic characteristics were investigated. X-ray diffraction analysis showed that the synthesized sample was in a single phase with a spinel-ferrite-like structure (space group Fd-3m). The scanning electron microscopy displayed homogenous spherical grains with an agglomeration of the particles. The chemical composition determined by energy-dispersive spectroscopy shows the absence of any impurities. To understand the role of magnetic interaction in MnFe2O4 spinel ferrites, the structural and magnetic properties of MnFe2O4 have been explored theoretically. Based on the first-principles methods via density functional theory and Monte Carlo simulations, the magnetic hysteresis cycle has been plotted. Using the generalized gradient and GGA-PBE approximation in the full-potential linearized augmented plane wave (FP-LAPW) method, the exchange coupling interactions between magnetic elements and local magnetic moment were evaluated. Furthermore, the theoretical magnetic properties of MnFe2O4 were found to match the experimental ones. They both revealed that MnFe2O4 is a soft ferromagnetic material. The theoretical curve of magnetization versus temperature indicates that the transition occurred at Tc = 580.0 K. This was also in good agreement with the experimental Curie temperature.